Changes and backlogs in the provision and utilization of essential health services in Afghanistan during and after the COVID-19 pandemic - Narges Neyazi; Ali Mirzazadeh; Abdul Ghani Ibrahimi; Ahmad Mirwais Ahmadzai; Jamshed Ali Tanoli (BMC Health Services Research)
Abstract Introduction Afghanistan is a low-income country where providing essential healthcare services is lifesaving for millions. The COVID-19 pandemic, the government and the international aid changes have affected the overburdened and fragile health system and put a risk on universal health coverage in Afghanistan. In this study, we aim to study the changes and backlogs to the essential health services during and after COVID-19 pandemic (Feb 2020 to Sep 2022) in Afghanistan. Method A cross-sectional study of health facilities was conducted in nine provinces of Afghanistan. A randomly selected 165 public and private primary care centers and hospitals in 49 districts were studied. A WHO standardized questionnaire was used for this survey. Trained staff met the facility managers in person and completed the questionnaire by individual interviews during September 2022. Result Hospitals located mostly in urban areas (n = 39, 65%) and clinics were located mostly in rural areas (n = 74, 71.1%) and governed by the government and the NGOs (76.6% of hospitals and 84.7% of clinics). The average number of staff per facility was 118 (SD = 180) for hospitals and 16(SD = 7) for clinics. 27 (46.5%) of hospitals and 44 (41.9%) of clinics reported that they experienced a higher outpatient service utilization in the previous month, compared to the month before. nearly half of the backlogs during the pandemic were related to routine preventive services such as annual check-ups antenatal care, and childhood immunization (55.0% for hospitals, and 45.7% for clinics). prioritizing high risk patients (86.7%), promoting self-care interventions wherever appropriate (75.0%), redirecting patients to alternative healthcare facilities (73.3%), providing all care in a single visit for multiple morbidities (60.0%), and providing home-based care for certain patients (58.3%) in hospitals. However, the most used strategies in clinics were prioritizing high risk patients (93.3%), redirecting patients to alternative healthcare facilities (75.2%), and providing home-based care for certain patients (66.7%). Conclusion The pandemic exacerbated existing health inequities and hindered progress toward Universal Health Coverage (UHC). Health facilities employed various strategies to cope with the disruptions, such as prioritizing high-risk patients, promoting self-care, and redirecting patients to alternative facilities. However, the increased cost of transportation and health services, along with limited availability of medicines, remained significant barriers to healthcare access.